The volunteer revolution unleashing the power of everybody - Hybels, Bill (Zondervan, 2004)
Maintains that the solution to the increasing economic pressure put upon the resources of local churches can be combatted by training, empowering, and inspiring volunteers, available due to the unprecedented spiritual openness in today's society.